2023
DOI: 10.1088/1751-8121/ace949
|View full text |Cite
|
Sign up to set email alerts
|

Algebraic approach and exact solutions of superintegrable systems in 2D Darboux spaces

Abstract: Superintegrable systems in 2D Darboux spaces were classified and it was found that there exist 12 distinct classes of superintegrable systems with quadratic integrals of motion (and quadratic symmetry algebras generated by the integrals) in the Darboux spaces. In this paper, we obtain exact solutions via purely algebraic means for the energies of all the 12 existing classes of superintegrable systems in four different 2D Darboux spaces. This is achieved by constructing the deformed oscillator realization and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Superintegrable systems in 2D Darboux spaces were classified [3,4] and it was found that there exist 12 distinct classes of second order superintegrable systems in the Darboux spaces. In [1] we presented exact solutions via purely algebraic means for the energies of all the 12 classes of superintegrable systems in four different 2D Darboux spaces. This was achieved by constructing the deformed oscillator realization and finite-dimensional irreducible representation of the underlying quadratic symmetry algebra generated by quadratic integrals respectively for each of the 12 superintegrable systems.…”
Section: Construction Of Representations Of Polynomial Algebrasmentioning
confidence: 99%
See 3 more Smart Citations
“…Superintegrable systems in 2D Darboux spaces were classified [3,4] and it was found that there exist 12 distinct classes of second order superintegrable systems in the Darboux spaces. In [1] we presented exact solutions via purely algebraic means for the energies of all the 12 classes of superintegrable systems in four different 2D Darboux spaces. This was achieved by constructing the deformed oscillator realization and finite-dimensional irreducible representation of the underlying quadratic symmetry algebra generated by quadratic integrals respectively for each of the 12 superintegrable systems.…”
Section: Construction Of Representations Of Polynomial Algebrasmentioning
confidence: 99%
“…Applying the deformed oscillator technique, in [1] we gave algebraic derivations of the spectra for the 12 superintegrable systems in the 2D Darboux spaces. As an example, we here review some of the results for the superintegrable system in the Darboux space II with the Hamiltonian Ĥ =…”
Section: Deformed Oscillator Algebra Realizationsmentioning
confidence: 99%
See 2 more Smart Citations